Impact of SLCO1B3 Ser112Ala Genetic Variation on Efficacy and Safety of Paclitaxel in Iraqi Women with Breast Cancer - Al-Hussein, Balsam Sabah Jawad; Al-Juhaishi, Atheer Majid Rashid; Abo Almaali, Hassan Mohamood Mousa; Alaskari, Ahmed Abduljabbar Jawad (Asian Pacific Journal of Cancer Biology, 2026)
Objective: This study intended to detect genetic polymorphism in active transporter SLCO1B3 Ser112Ala (rs4149117) and study the effect of this variation on efficacy and safety of paclitaxel in Iraqi women with breast cancer. Methods: The cross-sectional observational study was involved 150 women with breast cancer who received paclitaxel. These women were assessed individually in the 2nd week of paclitaxel therapy using a questionnaire to obtain demographic data, including age and body mass index, and the probability and severity of paclitaxel’s side effects. At the same time, neutrophilia count and breast cancer markers were assessed. Result: The wild type (TT) was detected in about 14% of breast cancer cases. While the mutant type (GG) and the heterozygous type (TG) were detected in about 65% and 21% of the cases, respectively. The results did not exhibit a significant difference among Iraqi breast cancer women who carried TT, TG, and GG genotypes regarding breast cancer markers (CA 15.3 and CEA) and paclitaxel related adverse effects (neutropenia, oral mucositis, and peripheral neuropathy) at P > 0.05. Conclusion: The SLCO1B3 334T>G genotyping was significantly distributed among Iraqi women with breast cancer. Still, there was no significant association between the SLCO1B3 334T>G genetic variation and efficacy and safety of paclitaxel.